2020
DOI: 10.34172/ijhpm.2020.94
|View full text |Cite
|
Sign up to set email alerts
|

Defining Delayed Discharges of Inpatients and Their Impact in Acute Hospital Care: A Scoping Review

Abstract: Background: With the ever-increasing demand on acute healthcare, the hospital discharge process and delayed discharges are considered relevant in achieving optimal performance in clinical settings. The purpose of this paper is to review the literature to identify conceptual and operational definitions of delayed discharges, identify causes and effects of delayed discharges, and also to explore the literature for interventions aimed at decreasing the impact (in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Procedural inefficiencies, including waiting for tests, investigations, and input from consult services, contribute to delays in discharges [ 27 , 28 ] A study examining causes of delayed discharge from the general medical wards of a metropolitan teaching hospital showed that 48.2% of patients experienced delays waiting for a service that extended their LOS [ 29 ]. The AMU received expedited access to imaging and diagnostic testing and interventions, which aided in timely decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural inefficiencies, including waiting for tests, investigations, and input from consult services, contribute to delays in discharges [ 27 , 28 ] A study examining causes of delayed discharge from the general medical wards of a metropolitan teaching hospital showed that 48.2% of patients experienced delays waiting for a service that extended their LOS [ 29 ]. The AMU received expedited access to imaging and diagnostic testing and interventions, which aided in timely decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively managing intermediate care capacity is especially important in times of high COVID-19 incidence. First, insufficient capacity puts severe pressure on upstream services, propagating ‘blockages’ in patient flow that, in turn, lead to increased stress on the (more expensive) acute care bed base, emergency department overcrowding, cancellation of elective procedures, and ambulance offload delays [ 10 , 11 ]. Second, delays to acute discharge are known to be associated with negative patient outcomes, including reduced physical and mental wellbeing and increased risk of nosocomial infections and cognitive decline [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effectively managing intermediate care capacity is especially important in times of high COVID-19 incidence. First, insufficient capacity puts severe pressure on upstream services, propagating 'blockages' in patient flow that, in turn, lead to increased stress on the (more expensive) acute care bed base, emergency department overcrowding, cancellation of elective procedures, and ambulance offload delays [5,6]. Second, delays to acute discharge are known to be associated with negative patient outcomes, including reduced physical and mental wellbeing and increased risk of nosocomial infections and cognitive decline [7].…”
Section: Introductionmentioning
confidence: 99%